Increasing interest and learning motivation SMP Swasta Anak Bangsa on science learning in the COVID-19 pandemic - Nurhabibah Nurhabibah; Ika Chastanti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Online learning during the COVID-19 pandemic generally reduces student interest in education. This study aims to analyze the factors causing the decline in students' interest and motivation and formulate solutions to solve them. This research is descriptive qualitative research. The data collection technique is done through intentional sampling, the data collection technique is done through interviews and questionnaires, and the data analysis technique uses the Miles and Huberman model. Based on the study's results, it is known that the increase in students' interest and motivation to learn science during the COVID-19 pandemic has not been fully achieved. Students have difficulty understanding the material taught by the teacher with a percentage of 86%, learning concentration difficulties at 84%, enthusiasm at 81%, and the level of boredom reaches 82%. The results of interviews with teachers and students showed that problems in understanding science learning activities were caused by the lack of interest and motivation of students and facilities and infrastructure, and caused by an unstable internet network. Therefore, motivation and interesting learning tools are needed to increase student interest in learning.Abstrak Pembelajaran online pada pada masa pandemi COVID-19 umumnya mengurangi minat belajar siswa. Penelitian ini bertujuan untuk menganalisis faktor-faktor penyebab menurunnya minat dan motivasi siswa, dan merumuskan solusi untuk menyelesaikannya. Penelitian ini merupakan penelitian deskriptif kualitatif, teknik pengumpulan data dilakukan melalui intensional sampling, teknik pengumpulan data dilakukan melalui wawancara dan angket, dan teknik analisis data menggunakan model Miles dan Huberman. Berdasarkan hasil penelitian diketahui peningkatan minat dan motivasi siswa untuk belajar IPA selama pandemi COVID-19 belum sepenuhnya tercapai, siswa mengalami kesulitan memahami materi yang diajarkan guru dengan persentase 86%, kesulitan konsentrasi belajar 84%, penyajian 81%, dan tingkat kebosanan mencapai 82%. Hasil wawancara dengan guru dan siswa menunjukkan bahwa kesulitan dalam memahami kegiatan pembelajaran IPA disebabkan oleh kurangnya minat dan motivasi siswa serta sarana dan prasarana serta disebabkan oleh jaringan internet yang tidak stabil. Oleh karena itu, diperlukan motivasi dan sarana belajar yang menarik agar dapat meningkatkan minat belajar siswa.